Josip Čerin in njegov študij muzikologije na Dunaju - Barbo, Matjaž (Muzikološki zbornik, 2017)
The paper focuses on Josip Čerin's musicological studies with Guido Adler in Vienna and analyses the source and meaning of his doctoral thesis on Slovenian Protestant music. In addition, it presents Čerin's efforts to promote symphonic music and his editorial work, thus showing how Čerin's work left a mark on his time and subsequent musicological efforts.
Keywords: biografije; Čerin, Josip; muzikologija; slovenski dirigenti; slovenski glasbeniki; slovenski muzikologi